2023
DOI: 10.1108/jrim-02-2023-0053
|View full text |Cite
|
Sign up to set email alerts
|

Immersive gaming in the fashion arena: an investigation of brand coolness and its mediating role on brand equity

Suha Fouad Salem,
Alshaimaa Bahgat Alanadoly,
Mohammed Ali Bait Ali Sulaiman

Abstract: PurposeThis study's aim was to investigate the role of the perceived values of gaming on consumers' perceptions of brands as cool as well as the impacts on the consumer–brand equity relationship. The study proposed a framework highlighting the influences of fashion-branded games on brand coolness and building fashion brands' overall equity. As significant factors affecting gamers, gender and gaming have been studied as moderators affecting the overall proposed framework.Design/methodology/approachA quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…On the other hand, brand equity was found to be influenced by consumers' perceptions of brand coolness. Consumers develop awareness, satisfaction, and loyalty towards fashion brands they perceive as cool (Salem et al, 2023a), which impacts their virtual-and maybe physical-consumption of those brands.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, brand equity was found to be influenced by consumers' perceptions of brand coolness. Consumers develop awareness, satisfaction, and loyalty towards fashion brands they perceive as cool (Salem et al, 2023a), which impacts their virtual-and maybe physical-consumption of those brands.…”
Section: Discussionmentioning
confidence: 99%
“…Gaining an understanding from studies on the entrepreneurial opportunity process is one approach to progressing the field's understanding of the effects of entrepreneurial alertness on success [40]. Although there are many different ways to conceptualize an entrepreneurial opportunity in the literature [41,42], hardly one prevalent theory holds a cognitive process that involves the act of identifying and then seizing an opportunity. Research has demonstrated that entrepreneurs can create opportunities or objectively find them [43,44].…”
Section: Entrepreneurial Alertness In Scanning Opportunitiesmentioning
confidence: 99%